Enzymatic quantification method with DNS for ß-mannanase in soybeans and in a nutritional additive - Ruiz Chatez, Danyerly Johana; Afanasjeva, Natalia (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In the search for the decrease in the use of antibiotics in animal feed, the development of nutritional additives that promote animal health and the best use of nutrients in plant-based foods has been reached. In this work, an analytical method was developed to quantify the activity of the enzyme endo-β-mannanase in a commercial nutritional additive and in soybeans commonly used as a feed source for pigs and chickens. The method used is based on the determination of reducing sugars with 3,5-dinitrosalicylic acid complemented with ultraviolet spectroscopy, where by means of a mannose calibration curve it is possible to determine the amount of sugars released by an equivalent unit of enzyme (U) in the raw material, in a commercial nutritional additive and when added in the soybeans. Additionally, the determination of the enzymatic activity was made by the method of liquid chromatography with an infrared detector, the signal of the mannose monosaccharide standard could be identified, but the separation, identification and subsequent quantification of the reducing sugars produced or released by the enzyme were not achieved enzyme activity in the feed matrix.